PENGARUH TEKNOLOGI INFORMASI DAN HASIL USAHA TERHADAP PERKEMBANGAN BISNIS UKM PADA PASAR SEGAR PENGAYOMAN KOTA MAKASSAR - Nadya Utari Gunawan; Mashur Razak; Ahmad Firman (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2020)
This study aims to determine whether the development of small medium entreprises is affected by information technology. The population in this study were business owners who used information technology at Pasar Segar Pengayoman, Makassar around 100 small medium entreprises. By using the Slovin formula, the number of samples was 50 respondents. This study uses multiple linear regression analysis by using IBM SPSS V 20 Statistics. The results of this study indicate that information technology and business results have a positive and significant partial effect toward business development.